Kinetics of the thermal degradation of patulin in the presence of ascorbic acid - Kokkinidou, S.; LaBorde, L. F.; Floros, John D. (My University, 2014)
Degradation of the mycotoxin patulin between 25 and 85 °C without and with added ascorbic acid was studied, and the effectiveness of linear and nonlinear models for predicting reaction rates was compared. In agreement with previous reports, ascorbic acid significantly increased (P ≤ 0.05) the rate of patulin degradation at all temperatures studied. The data for patulin degradation in the absence of ascorbic acid were adequately modeled using a zero-order linear kinetic model. However, the predictive abilities of zero and higher-order linear models were not adequate to describe the more complex reactions that likely occurred when ascorbic acid was added. In contrast, the nonlinearWeibull model adequately described the patulin-ascorbic acid reaction throughout the temperature range studied. Zero-order rate constants and Weibull scale values for each of the respective reactions followed the Arrhenius law. Activation energies of 58.7 ± 3.9 and 29.6 ± 1.9 kJ mol⁻¹ for the reaction without and with ascorbic acid, respectively, confirmed decreased patulin stability in the presence of ascorbic acid and suggested that the mechanisms for the 2 degradation reactions were different.
Keywords: Ascorbic acid; Kinetics; Patulin; Thermal degradation; Weibull model